2021
DOI: 10.1111/exsy.12898
|View full text |Cite
|
Sign up to set email alerts
|

New entropy propositions for interval‐valued spherical fuzzy sets and their usage in an extension of ARAS (ARAS‐IVSFS)

Abstract: The spherical fuzzy set (SFS) concept and its interval-valued version (IVSFS) are among the recent developments aiming at handling the hesitancy representation issue in multiple attribute decision-making problems. In SFS, decision-makers can assign independent membership, non-membership, and hesitancy degrees. IVSFS extends this feature by assigning intervals to these three degrees. In this manner, the uncertainty, vagueness, and ambiguity hidden in human judgements can be quantified and processed more compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…SFS has garnered attention from the researchers for extensive use in solving various real-life issues like medical diagnosis problem using trigonometric similarity measures and Choquet integral-based SF operation [54]; 3D printer selection using interval valued SF-additive ratio assessment (ARAS) method [55]; waste disposal location selection using SF-REGIME approach [56]; insurance policy selection using SF bi-objective linear decision-making model [57]; SF-analytic hierarchy process for supplier selection [58]; process mining application with SF-AHP [59]; energy management using SF linear Diophantine fuzzy soft rough sets [60]; cosine similarity-based medical diagnosis [61]; advertisement strategy formulation with SF-TOPSIS method [62]; Earth science application with SF [63]; SF-based failure mode and effect analysis in marble manufacturing [64]; assessment of efficacies of Facebook ads using SF-VIKOR in a group decision-making setup [65]; present value analysis in wealth management [66]; agricultural management in Industry 4.0 using interval-valued SF [67]; hospital performance evaluation using interval-valued SF-AHP [68]; and fraud detection with interval-valued AHP-MULTIMOORA method [69], among others. We have found that though there is an increasing number of applications of SFS in variety of areas, there is scope for further extensions of existing MCDM algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…SFS has garnered attention from the researchers for extensive use in solving various real-life issues like medical diagnosis problem using trigonometric similarity measures and Choquet integral-based SF operation [54]; 3D printer selection using interval valued SF-additive ratio assessment (ARAS) method [55]; waste disposal location selection using SF-REGIME approach [56]; insurance policy selection using SF bi-objective linear decision-making model [57]; SF-analytic hierarchy process for supplier selection [58]; process mining application with SF-AHP [59]; energy management using SF linear Diophantine fuzzy soft rough sets [60]; cosine similarity-based medical diagnosis [61]; advertisement strategy formulation with SF-TOPSIS method [62]; Earth science application with SF [63]; SF-based failure mode and effect analysis in marble manufacturing [64]; assessment of efficacies of Facebook ads using SF-VIKOR in a group decision-making setup [65]; present value analysis in wealth management [66]; agricultural management in Industry 4.0 using interval-valued SF [67]; hospital performance evaluation using interval-valued SF-AHP [68]; and fraud detection with interval-valued AHP-MULTIMOORA method [69], among others. We have found that though there is an increasing number of applications of SFS in variety of areas, there is scope for further extensions of existing MCDM algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…In what follows are some of the recent past applications of SFS in complex decision making. SFS has been used in various real-life decision making context, such as promotional strategy design (Farrokhizadeh et al, 2021), supplier selection problem (Sharaf, 2021), investment decision making (Seyfi-Shishavan et al, 2021), healthcare such as medical diagnosis (Unver et al, 2022;Mahmood et al, 2021), energy management (Hashmi et al, 2021, selection of 3D printers (Aydoğdu and Gül, 2021), process mapping (Dogan, 2021;Gul and AK, 2021), waste disposal location selection (Oztaysi et al, 2022) and agricultural engineering and management (Erdoğan, 2022) among others. In that respect, application of SFS in psychological assessment is quite rare in the literature.…”
Section: Related Work On Sfsmentioning
confidence: 99%
“…(2021) presented a spherical fuzzy method that integrates maximum deviation and TOPSIS. Aydoğdu and Gül (2022) developed a novel entropy proposition for SFSs. Nguyen et al.…”
Section: Literature Reviewmentioning
confidence: 99%